New Upper Bounds for the Heights of Some Light Subgraphs in 1-Planar Graphs with High Minimum Degree - Xin Zhang; Jian-Liang Wu; Guizhen Liu (Discrete Mathematics & Theoretical Computer Science, 2011)
Combinatorics